2005
DOI: 10.1246/cl.2005.802
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Trichlorobenzene with Different Radicals Generated by Alternating Current Electrolysis in Aqueous Solution

Abstract: Trichlorobenzenes can be easily decomposed by alternating current electrolysis in aqueous solution. The mechanism of the decomposition was found to be based on selective redox reactions with different radicals—hydrogen atoms and hydroxyl radicals—generated by water electrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Even though it has been suggested that AC-polarization may induce isomerization and production of radicals or could induce oxidations and reductions in organic functions of the enzyme [10][11][12], we believe that most of the changes we observe are due to a change in pH and temperature of the solution. The pH and temperature change would induce structural modifications in the AC treated enzyme, which is reflected in the UV-vis, FT-IR and UV-CD measurements.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Even though it has been suggested that AC-polarization may induce isomerization and production of radicals or could induce oxidations and reductions in organic functions of the enzyme [10][11][12], we believe that most of the changes we observe are due to a change in pH and temperature of the solution. The pH and temperature change would induce structural modifications in the AC treated enzyme, which is reflected in the UV-vis, FT-IR and UV-CD measurements.…”
mentioning
confidence: 66%
“…Electrolysis with a periodically varying current has been used in anodic dissolution, anodizing and corrosion processes [1]; electrodeposition [2,3] heating systems [4,5]; ohmic sterilization [6]; degradation of inorganic and organic pollutants such as NO and naphthalene [7][8][9][10] and in the synthesis and chemical isomerization of metal-organic complexes [11,12]. Recently, alternating current (AC) was used for the electrophoretic deposition (EPD) of biomolecules suspended in aqueous dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Advanced Oxidation Processes (AOPs) based on the generation of highly reactive species, such as hydroxyl or sulfate radicals (OH • or SO 4 −• ), are efficient remediation methods [ 14 , 15 , 16 ]. The oxidation of TCBs with sodium persulfate [ 17 ], Fenton’s reagent [ 18 ], ozone [ 19 ], photocatalysis [ 20 , 21 ], electrochemical processes [ 22 ], and catalytic wet oxidation (CWO) [ 23 , 24 ] have been studied. More recently, UV light has been proven to enhance TCB oxidation by persulfate [ 25 ] or hydrogen peroxide [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant phenol production should differ from that obtained using a DC supply. The advantage of AC electrolysis over DC electrolysis has been reported for the purification of organic pollutants [16,17] and for the synthesis of chemicals. [18,19] Based on these observations and assumptions, it is expected that the electrochemical synthesis of phenol could be improved by optimizing the AC frequency for Reactions (1), (2), (3), and (4).…”
mentioning
confidence: 99%